Fermions in electroweak baryogenesis - Mou, Zong-Gang (2015)
We study the chiral anomaly by solving the Dirac equation for fermions in parallel electric and magnetic fields. In such case, only the lowest-energy Landau levels are relevant to the anomaly. Specifically, for massless fermions, the chiral anomaly is a result of the production of particles of one chirality, and no creation of particles of the other chirality. For massive fermions, we find that the chiral anomaly equation can be simply obtained via a proper regularization of the range of the momentum. We extend the method to anomaly cancellation, and conclude that the conservation of the baryon number plus lepton number must be violated as a quantum anomaly in the context of the Standard Model. Accordingly, such baryon number non-conservation can play a vital role during the electroweak transition to achieve the baryon asymmetry of the Universe.